Analysis of High School Students’ Difficulties in Solving Mathematics Story Problems on Opportunity Material - Revika Nofriani; Rahmadini Fitri; Lilis Marina Angraini; Tengku Abdani Murazanty; Kyaruzi, Florence (EDUPEDIA Publisher, 2024)
This research aims to describe the difficulties experienced by students in solving mathematics story problems on opportunity material. The type of research used is a descriptive method with a qualitative approach. The study involved 30 students in class XII IPS 2 SMA Negeri 2 in Pekanbaru. Data were collected using a combination of tests and interviews. The overall research procedure involved three stages, namely the planning stage, implementation stage, and conclusions. Data were analysed using descriptive statistics. The results of this study show that students’ experienced difficulties in solving mathematics story problems on opportunity material especially in understanding the problem (33,33%), carrying out transformations (36,66%), processing skills (38,88%), and difficulty in drawing conclusions (51,11%).